INFRASTRUCTURE POLICY OF THE CASPIAN STATES: DEVELOPMENT STRATEGY AND GEOPOLITICAL AIMS - ZHILTSOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2021)
In recent years, the Caspian states have been paying increasingly more attention to port infrastructure development. The construction of new facilities and the reconstruction of existing ports received a new impetus. The Caspian states increase their investments in this sphere every year. They have developed national programs that aim to increase the volume of cargo passing through the Caspian states’ seaports.The development of port infrastructure, augmented by new railways, was deliberated by the Caspian states in the context of solving geopolitical problems. The advancement of the negotiation process on the Convention on the Legal Status of the Caspian Sea brought the solution of economic issues to the fore, along with the development of transport and related infrastructure. The signing of this document in August 2018 only raised the interest of the regional states in trade and economic cooperation. Accordingly, one of the key tasks that the Caspian states were facing was port infrastructure development. The construction of new ports was believed to foster achievement of long- term goals. In addition to economic development,